Honky tonk time machine [compact disc] - Strait, George, 1952- (MCA Nashville, 2019)
The King of Country Music, George Strait is set to release his brand new studio album on March 29th. This will be his first album of all-new material in four years and has thirteen brand new tracks including the first single 'Every Little Honky Tonk Bar.' The album will feature one track with a duet with Willie Nelson, as well as the powerful song 'God and Country Music.'